MEMAHAMI MIGRASI PEKERJA INDONESIA KE LUAR NEGERI - Sukamdi Sukamdi (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 2007)
There are evidence of growing Indonesian labour migration flows overseas. This involves at least two other important issues. The first one is the increase of undocumented (illegal) international migration from Indonesia, mostly to neighboring countries. Second, feminization of labour migration is also expected to grow to responses consequences on both macro and micro level. Many of them have been well addressed in research, but still left some important issues, such as trafficking and children left behind. Several researches have been conducted in there two subjects, but still limited. In fact they are very important in developing a more sound policies to alleviate the negative impact of international labour migration.